2022
DOI: 10.3390/life12101670
|View full text |Cite
|
Sign up to set email alerts
|

Atopic Dermatitis with Multiple Comorbidities Treated with Dupilumab. A Case Report and Review of the Literature Regarding the Safety of Dupilumab

Abstract: Dupilumab is the only available biological treatment for moderate-to-severe atopic dermatitis (AD). Even so, limited clinical data regarding its safety profile are available. Interactions with other drugs and the adverse effects of Dupilumab on patients with multiple comorbidities, such as chronic heart disease, diabetes, chronic kidney disease, etc., are not known yet. Moreover, there have been described cases of cutaneous lymphomas induced by Dupilumab. Therefore, the clinician that wants to start treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Although blocking this common receptor for the two ILs brings significant clinical benefits in atopic dermatitis, this benefit is not found for all pathologies in which IL-4 and IL-13 intervene, as a recent study suggests that IL-4/IL-13’s anti-inflammatory properties could be useful for inflammatory arthritis treatment [ 36 ]. Additionally, in one of our own studies regarding the use of Dupilumab for AD treatment, we found that the use of this drug can lead to the progression of myeloproliferative disorders in patients in which the underlying disease is misdiagnosed as AD [ 37 ]. As we showed in the current study, inhibition of the receptor for IL-4 and IL-13 leads to an increased serum concentration of both ILs.…”
Section: Discussionmentioning
confidence: 99%
“…Although blocking this common receptor for the two ILs brings significant clinical benefits in atopic dermatitis, this benefit is not found for all pathologies in which IL-4 and IL-13 intervene, as a recent study suggests that IL-4/IL-13’s anti-inflammatory properties could be useful for inflammatory arthritis treatment [ 36 ]. Additionally, in one of our own studies regarding the use of Dupilumab for AD treatment, we found that the use of this drug can lead to the progression of myeloproliferative disorders in patients in which the underlying disease is misdiagnosed as AD [ 37 ]. As we showed in the current study, inhibition of the receptor for IL-4 and IL-13 leads to an increased serum concentration of both ILs.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Clinical trials for dupilumab did not include patients with cancer, and current immunosuppressive agents used for the treatment of AD raise safety concerns when being used for patients with malignancies with the possibility of exacerbation of cancer, although several recent reports have found no evidence linking dupilumab with cancer recurrence. [11][12][13] There are many components to the tumour microenvironment (TME) in epithelial cancers, including fibroblasts, immune and inflammatory cells, blood and lymph vessels, and nerves, all with the potential to influence tumour behaviour. Tumour-associated macrophages are particularly plentiful at all stages of tumour growth, and these have been shown to facilitate angiogenic responses and promote tumour proliferation.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 Clinical trials for dupilumab did not include patients with cancer, and current immunosuppressive agents used for the treatment of AD raise safety concerns when being used for patients with malignancies with the possibility of exacerbation of cancer, although several recent reports have found no evidence linking dupilumab with cancer recurrence. 11 , 12 , 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation